How much does it cost to include a marginal rural area as a Natura 2000 site? Social cost and expenditures for compensation schemes - Barreiro, J.=700 1 Soler, F.; Perez y Perez, L.
(Es, En)
ilus., 36 ref.
Keywords: ANALISIS DE COSTOS Y BENEFICIOS; GESTION; CONSERVACION DE LA NATURALEZA; MEDIO AMBIENTE; ZONAS DESFAVORECIDAS; ESPAÑA; PAGOS COMPENSATORIOS